The prophets of Israel - Kratz, Reinhard Gregor (Critical studies in the Hebrew Bible, 2015)
"The book offers an up-to-date and readable introduction to the manifold literary and historical problems of biblical prophecy. Reinhard Gregor Kratz provides the reader with a clear analysis of the development of the institution of prophecy in ancient Israel and Second Temple Judaism. Through a close reading of the prophetic corpus he demonstrates that in biblical tradition we have to distinguish between the historical and the literary prophet"--